Education as a Strategic Instrument for Human Rights Protection: Innovations and European Best Practices - Yevhen Leheza; Nataliia Zadyraka; Yuliia Leheza (Nusantara Education, 2026)
Education has increasingly become a strategic instrument for promoting, implementing, and safeguarding human rights amid rapid social transformation and democratic development. However, despite ongoing educational reforms, human rights education in Ukraine remains fragmented and insufficiently aligned with European standards, limiting its contribution to fostering legal awareness and democratic citizenship. This study aims to examine the role of education in ensuring human rights, analyze the implementation of human rights education across selected European Union countries, identify transferable best practices, and formulate policy recommendations to strengthen Ukraine's educational framework in line with European standards. This research employed a qualitative field research design using a comparative legal approach. Empirical data were collected through semi-structured interviews with educators, legal scholars, policymakers, and curriculum developers in Ukraine, complemented by field observations of educational institutions and document analysis of national legislation, educational policies, and European normative frameworks. The findings reveal that Germany, France, Finland, and Poland have institutionalized human rights education as an integral component of compulsory civic education through interdisciplinary curricula, participatory learning methods, teacher professional development, and digital educational resources. By contrast, Ukraine continues to implement human rights education inconsistently across educational levels, resulting in uneven legal literacy and civic competence. The study further demonstrates that adapting European educational practices requires contextualization within Ukraine's legal, institutional, and socio-cultural environment, supported by curriculum reform, teacher capacity building, digital innovation, and strengthened cooperation with European and international organizations. The originality of this research lies in integrating empirical field evidence with comparative legal analysis to develop a comprehensive framework for reforming human rights education in Ukraine. These findings advance legal education scholarship and provide practical guidance for policymakers, educational institutions, and curriculum developers seeking to modernize national education systems while reinforcing democratic values and sustainable human rights protection.